Modelling different strategies to prevent coronary heart disease in primary care. - Silagy, C; Mant, D; Carpenter, L; Muir, J; Neil, A (1994)
Strategies for prevention of coronary heart disease (CHD) in primary care need to take into account the number of people who require screening, further assessment, intervention and follow-up (i.e. the patient workload generated for the general practitioner) as well as the anticipated reductions in morbidity and mortality. Risks of CHD for various risk profiles were estimated from equations produced by the Framingham study. This enabled an estimate of the number of avertable CHD events to be compared against the patient workload implications for the general practitioner when different screening and intervention strategies were used. The Framingham equations were applied to a population of 5727 men and women aged 35-64 years of age registered with general practices in the south of England. Adopting an unselective approach to screening resulted in 14.1% (n = 73) of the 517 CHD events predicted over a 10 year period being averted. A limited screening strategy, involving 25% (n = 1436) of the patients would avert 5.6% (n = 29) of the predicted CHD events, whilst more extended strategies involving between 37% (n = 2131) and 46% (n = 2660) of the practice population respectively would result in between 6.9% (n = 36) and 9.3% (n = 48) of events being averted. The marginal benefit in averting CHD events decreased as more screening criteria were included. Almost all (99%) of the people identified by the selective screening strategies would require some form of intervention, predominantly lifestyle advice. Lowering the systolic blood pressure by 15 mmHg instead of 10 mmHg was equally effective as a 5% improvement in the overall rate of smoking cessation.(ABSTRACT TRUNCATED AT 250 WORDS)